2019
DOI: 10.1016/j.amjmed.2019.01.030
|View full text |Cite
|
Sign up to set email alerts
|

The State of Ambulatory Undergraduate Internal Medicine Medical Education: Results of the 2016 Clerkship Directors in Internal Medicine Annual Survey

Abstract: AAIM is the largest academically focused specialty organization representing departments of internal medicine at medical schools and teaching hospitals in the United States and Canada. As a consortium of five organizations, AAIM represents department chairs and chiefs; clerkship, residency, and fellowship program directors; division chiefs; and academic and business administrators as well as other faculty and staff in departments of internal medicine and their divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…One of the prerequisites for the successful implementation of outpatient education is a clinic with adequate space and minimal necessary equipment [ 22 ]. Despite this, there is no established standard for the equipment and accommodations an academic outpatient clinic should have [ 2 , 23 ], and a lack of suitable sites has been cited as a source of dissatisfaction in numerous studies [ 12 , 24 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the prerequisites for the successful implementation of outpatient education is a clinic with adequate space and minimal necessary equipment [ 22 ]. Despite this, there is no established standard for the equipment and accommodations an academic outpatient clinic should have [ 2 , 23 ], and a lack of suitable sites has been cited as a source of dissatisfaction in numerous studies [ 12 , 24 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted numerous professional societies, such as the “American College of Physicians (ACP),” the “Society of General Internal Medicine (SGIM),” and the “American Association of Medical Colleges,” as well as accrediting bodies, such as the “Liaison Committee on Medical Education and the Higher Learning Commission,” to advocate for the expansion and further development of ambulatory education [ 1 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The proportion of medical schools that incorporate GIM ambulatory time into their core (third year) rotations has increased from 85% in 2013 to 99% in 2017. 6,7 Notably, 48% of that GIM experience occurred in interdepartmental primary care rotations with other specialties such as family medicine and pediatrics. 6 In 2017, clerkship directors reported that time in GIM clinic ranged from 15 half days in the traditional block model to 31 half days as part of longitudinal integrated clerkships.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Notably, 48% of that GIM experience occurred in interdepartmental primary care rotations with other specialties such as family medicine and pediatrics. 6 In 2017, clerkship directors reported that time in GIM clinic ranged from 15 half days in the traditional block model to 31 half days as part of longitudinal integrated clerkships. 8 Despite increased attention to outpatient training in medical school, one IM residency program reported that only 15% of interns from a diversity of medical schools felt they received sufficient training in medical school to prepare them for their continuity clinic.…”
Section: Introductionmentioning
confidence: 99%